Use of facial authentication in E-learning: a study of how it affects students in different Spanish-speaking areas. - Guillén-Gámez, Francisco David; García-Magariño, Iván (Inderscience, 2015)
The authentication of students in E-learning is relevant to verify the assessment of distance learning students. Among diverse technologies for recognition, facial authentication (by means of biometrics) allows user identities to be corroborated and certified focusing on their facial physiological characteristics. The demand of students wishing to achieve admission to E-learning programs is actually high. Subsequently, it is essential for this type of education to be as respectable and recognised as any other. For this purpose, it would be essential to check the students’ identities while doing their homework using learning management systems such as Moodle platform. The main objective of this study is the analysis of student impressions concerning the development and implementation of facial verification for E-learning within the Moodle platform in different Spanish speaking areas like Spain and Latin America. A survey was carried out among the students after using the facial authentication tool within Moodle. The survey of 67 students from Masters produced high satisfaction scores about the acceptance of facial authentication as an improvement technique for distance education. Nevertheless, in general Spanish students reached lower average levels compared to Latin American students. These differences are statistically analysed to show their significance.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/4573
Keywords: Biometría; Educación - Innovaciones tecnológicas; Reconocimiento facial (Informática); Tecnología educativa; Analysis of perceptions; Biometric recognition; Biometrics; Blended learning; Distance education; Educational results; Face recognition; Facial authentication; Learning management system; Moodle; Online learning; University